Alcohol and road safety: investigation and legal aspects - A. K. Jaiswal; Supriya Krishna; Amit Agrawal; Amrita Ghosh; Ranabir Pal (Al Ameen Medical College, 2018)
Background: Ethanol (commonly phrased as Alcohol), in spite of presence of so many 'recreational drugs', is the most common drug exploited throughout the world. Objectives: This study explored the deleterious role of alcohol, effect of its consumption and their legal implications in a systematic manner. Method: To assess the toxic role of alcohol with the effects of its consumption and their legal implications a systematic review was done through an extensive search in the books, indexed literature and website-based reports, 14 reported literatures were identified of alcohol use. Results: Alcohol acts as a central nervous system depressant of specialised and sensitive cells of cerebral cortex. Its adverse effects like decrease in cognitive and psychomotive skills are well documented, with special regard to driving performance. In presence of lacunae in the implementation of legal enforcements alcohol related road safety has to be research interest to reduce this preventable morbidity. Ethanol and its role as a central nervous system depressant is well documented. In the last decade, drastic changes in the age of initiation as well as the bridging of gender based gap in alcohol use have been observed. Conclusion: Alcohol related road traffic injuries are major threat to civilization including premature deaths on road with uncountable quantity and quality of socioeconomic effects on family as well as the community that need to be prevented by the holistic approach.